First impressions: Hobbes on religion, education, and the metaphor of imprinting - Bejan, TM (Oxford University Press, 2018)
The metaphor of ‘imprinting’ used to describe the process of education in Leviathan has long captured the imagination of commentators inclined to view Hobbes as a harbinger of modern totalitarianism. And yet its significance for recent scholarly debates about a ‘more tolerant’ Hobbes has been ignored. This chapter examines Hobbes’s metaphor in the broader context of his life and works in order to understand its implications for the sovereign’s role in regulating religion, not only outwardly, but in foro interno as well. Doing so reveals imprinting, like all of Hobbes’s metaphors, to have been carefully chosen. As a play both on a Platonic pedagogical analogy and the Pauline maxim, ‘Faith cometh by hearing’, it reflects Hobbes’s sensitivity to the curious moment in which he wrote—a moment in which the rise of a new culture of mass media and older traditions of philosophical and religious reflection on education would collide.